RISK FACTOR OF THE INCIDENCE OF DIABETES MELITUS IN THE PRODUCTIVE AGE - Arnida, Arnida; Akhmad Dwi Priyatno; Ali Harokan (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
The high incidence of diabetes mellitus in productive age has become a major public health problem in Indonesia. This study aims to analyze the relationship between age, education, obesity, physical activity, hypertension, family history of DM, and smoking with the incidence of Type 2 diabetes mellitus in the work area at UPTD Pauh Community Health Center, North Musi Rawas Regency. This type of research is quantitative with a cross sectional design. The sampling technique used was accidental sampling. The sample in this study was a portion of Diabetes Mellitus patients seeking treatment at the UPTD Pauh Community Health Center, North Musi Rawas Regency, totaling 98 people. Data collection was carried out using a questionnaire. Data were analyzed using Univariate, Bivariate and Multivariate analysis. Based on the research results, it was found that there was a relationship between age (0.017), education (0.001), obesity (0.012), physical activity (0.001), hypertension (0.000), family history of DM (0.000), and smoking (0.000) with the incidence of Type 2 diabetes mellitus. in the Working Area at the UPTD Pauh Community Health Center, North Musi Rawas Regency. The results of the multivariate analysis show that the family history of DM variable is the most dominant variable in the incidence of Type 2 DM. The conclusion in this study is that there is a relationship between age, education, obesity, physical activity, hypertension, family history of DM, and smoking and the dependent variable, namely the incidence Type 2 diabetes mellitus